2018
DOI: 10.18343/jipi.23.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Field Water Balance with Production of PB260 Rubber Clone

Abstract: ABSTRAK Secara umum produksi karet dipengaruhi oleh fluktuasi curah hujan setiap bulan. Penelitian bertujuan mengetahui pengaruh curah hujan, evapotranspirasi, dan ketersediaan air lahan terhadap produksi karet klon PB260. Penelitian ini dilaksanakan di Kebun Percobaan Balai Penelitian Sembawa, Sumatera Selatan pada tahun 20132016. Plot penelitian yang digunakan adalah tanaman menghasilkan klon PB260 tahun tanam 2002 dengan tekstur tanah clay loam. Penelitian ini dilakukan dengan cara membandingkan produksi t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Hence the rubber plants are able to extract it from the soil easily. Some research showed that the rubber yield is influenced by fluctuation of rainfall as well as soil water content [6,7]. The low soil water content resulted in drought stress that affected the decrease of stomatal conductance, transpiration rate, and photosynthesis rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence the rubber plants are able to extract it from the soil easily. Some research showed that the rubber yield is influenced by fluctuation of rainfall as well as soil water content [6,7]. The low soil water content resulted in drought stress that affected the decrease of stomatal conductance, transpiration rate, and photosynthesis rate.…”
Section: Introductionmentioning
confidence: 99%
“…Hence the growth rate and yield were decreased [8,9]. For example, the El-Nino phenomenon in 2015 caused a prolonged dry season in South Sumatera that resulted in the decrease of three years old rubber clone PB 260 girth growth rates as high as 65% and the decrease of clone BPM 24 rubber yield [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…Rubber-based intercropping systems offers a practical solution to this issue and increasing overall productivity [3,25]. Benefits of intercropping system between rubber and intercrops compared to monoculture system of rubber are as follows: 1) low weed growth in rubber area [4,5,6,7]; 2) larger girth rubber in intercroping system [8,9,10,11,12]; 3) increased yiled of rubber [13,14]; 4) increase in soil organic matter [15,16]; and 5) increased farmers income [2,10,17].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, Indonesia farmers plant rubber using single row with a planting distance of 6 m x 3 m (550 trees / ha), or 7 m x 3 m (476 trees / ha) [1,6,10]. Under these planting system, intercrops can only be planted until rubber plants are 1 to 2 years old [18,6,7,10], as the canopies of adjacent rows would have closed by then and the light is light intensity under the canopy would only be 50-60% [19,20]. The area that can be used for intercropping is around 50-60% of rubber total area [19].…”
Section: Introductionmentioning
confidence: 99%